Phase equilibria and thermodynamic evaluation of the Ti-V-O system in air. (December 2018) - Malan, Willem Dutoit; Akdogan, Guven; Taskinen, Pekka; Hamuyuni, Joseph; Zietsman, Johan
Abstract: The Ti-V-O system was studied experimentally from 700 °C to 1500 °C by high-temperature equilibration, quenching, scanning electron microscope and Energy-Dispersive X-Ray spectroscopy. The solubility of titanium in the slag is less than 3 mol% at 1500 °C and the vanadium solubility in the rutile phase reached a maximum of 7.8 mol% at 1400 °C. The thermodynamic evaluation was performed with FactSage 7.0. The solubility of vanadium in the rutile phase was developed within the framework of the compound energy formalism. The properties of the liquid phase were described with the quasichemical model. A set of self-consistent thermodynamic parameters was estimated well within acceptable limits. The calculated phase diagram of the Ti-V-O system in air is presented and compared to experimental observations and other phase diagram data from literature.